Keep focussing: striatal dopamine multiple functions resolved in a single mechanism tested in a simulated humanoid robot - Fiore, Vincenzo G.; Sperati, Valerio; Mannella, Francesco; Mirolli, Marco; Gurney, Kevin; Friston, Karl; Dolan, Raymond J.; Baldassarre, Gianluca (Frontiers in Psychology, 2014)
The effects of striatal dopamine (DA) on behavior have been widely investigated over the past decades, with ``phasic'' burst firings considered as the key expression of a reward prediction error responsible for reinforcement learning. Less well studied is tonic DA, where putative functions include the idea that it is a regulator of vigor, incentive salience, disposition to exert an effort and a modulator of approach strategies. We present a preliminary model combining tonic and phasic DA to show how different outflows triggered by either intrinsically or extrinsically motivating stimuli dynamically affect the basal ganglia by impacting on a selection process that this system performs on the inputs provided by the targeted cortex. The model, which has been tested on the simulated humanoid robot iCub in the interaction with a mechatronic board, shows the putative functions ascribed to DA emerging from the combination of a standard computational mechanism coupled to a differential sensitivity to the presence of DA across the striatum.